2022
DOI: 10.1111/jcpt.13619
|View full text |Cite
|
Sign up to set email alerts
|

Association of orexin receptor antagonists with falls during hospitalization

Abstract: Falling is a common occurrence during hospitalization. It has also been reported that activities of daily life are decreased by repeated falls, 1 and preventing falls among hospitalized patients is a key goal of hospital management. The factors of falls can be divided into two types. [2][3][4] Extrinsic risk factors cover the individual's environment, such as the use of assistive devices and walking aids and the absence of handrails. Intrinsic risks factors include the number of drugs taken, muscle weakness, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Falls, a common concern in the older population, which may be precipitated by some hypnotic drugs prescribed for insomnia [ 25 , 50 , 51 ], were infrequent. Specifically, the number of falls was numerically lower in patients receiving daridorexant (either dose) than in those receiving placebo, as suggested with other DORAs [ 52 ]. Daridorexant, like other approved DORAs, has been designated as a schedule IV-controlled substance by the US Drug Enforcement Agency.…”
Section: Discussionmentioning
confidence: 79%
“…Falls, a common concern in the older population, which may be precipitated by some hypnotic drugs prescribed for insomnia [ 25 , 50 , 51 ], were infrequent. Specifically, the number of falls was numerically lower in patients receiving daridorexant (either dose) than in those receiving placebo, as suggested with other DORAs [ 52 ]. Daridorexant, like other approved DORAs, has been designated as a schedule IV-controlled substance by the US Drug Enforcement Agency.…”
Section: Discussionmentioning
confidence: 79%
“…As in our previous studies, both benzodiazepines and non-benzodiazepines were included among hypnotic medications, except for melatonin receptor agonists and orexin receptor antagonists because these drugs have fewer side effects that cause falls. 27 , 28 If an inpatient experiences a fall, a nurse in charge of the patient or who finds the patient completes an incident/accident report. The number of falls was calculated using these reports.…”
Section: Methodsmentioning
confidence: 99%
“…Although some countries offer melatonin as an over-the-counter drugs or supplements, it is not available in Japan. Previous studies have shown that ramelteon, a melatonin receptor agonist, does not have a significant effect on falls or fractures [ 15 17 ]. However, we found that melatonin receptor agonists increased the risk of femoral fractures in patients with PD, which may be attributed to physician bias, where melatonin receptor agonists are prescribed to patients who are at a high risk of falls because these drugs are less likely than benzodiazepines and non-benzodiazepines to cause falls.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in older adults showed that suvorexant, an orexin receptor antagonist, is associated with a lower risk of falls than placebo; however, somnolence was more common with suvorexant than with placebo [ 20 ]. Another previous study demonstrated that lemborexant, another orexin receptor antagonist that was approved in Japan in 2020, significantly lowered the risk of falls [ 17 ]. In contrast, we found that orexin receptor antagonists did not increase the risk of injuries.…”
Section: Discussionmentioning
confidence: 99%